2022
DOI: 10.11609/jott.7643.14.2.20689-20691
|View full text |Cite
|
Sign up to set email alerts
|

Geodorum laxiflorum Griff. (Orchidaceae), a new distribution record for Maharashtra state of India

Abstract: Geodorum laxiflorum Griff., an endemic orchid of India is collected for the first time in Maharashtra state. Gadchiroli district is a much known district of the state for its rich biodiversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In the protologue of G. laxiflorum , Griffith (1845) described the labellum with a patch of purplish, short cellular hairs on the adaxial surface near the base. These hairs are too tiny to be seen properly even with modern dissecting stereo microscope and thus, this character has not been described by subsequent workers (Seidenfaden 1983, Misra 2004, 2014, Bhatt et al 2015, Veeranjaneyulu et al 2017, Bhoyar et al 2022). During our study we observed not only the microscopic cellular hairs near the base of the labellum, but also a variation in their colour, ranging from purplish or purplish‐brown to creamy white and white (Fig.…”
Section: Taxonomic Treatmentmentioning
confidence: 93%
See 3 more Smart Citations
“…In the protologue of G. laxiflorum , Griffith (1845) described the labellum with a patch of purplish, short cellular hairs on the adaxial surface near the base. These hairs are too tiny to be seen properly even with modern dissecting stereo microscope and thus, this character has not been described by subsequent workers (Seidenfaden 1983, Misra 2004, 2014, Bhatt et al 2015, Veeranjaneyulu et al 2017, Bhoyar et al 2022). During our study we observed not only the microscopic cellular hairs near the base of the labellum, but also a variation in their colour, ranging from purplish or purplish‐brown to creamy white and white (Fig.…”
Section: Taxonomic Treatmentmentioning
confidence: 93%
“…The most significant variation is in the relative length of the floral bract with respect to the pedicel plus ovary. Griffith (1845), Bhatt et al (2015), Veeranjaneyulu et al (2017) and Bhoyar et al (2022) described/illustrated bracts which were shorter than the pedicel plus ovary. During our study we have observed bracts which are shorter to longer than the pedicel plus ovary, even in plants from the same subpopulation.…”
Section: Morphological Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…It turned out to be a new record and together they published a scientific paper on this occurrence. So Saduram, with little formal education, is now a card-carrying member of the scientific community (Bhoyar et al, 2022).…”
Section: Tribals In the Knowledge Agementioning
confidence: 99%